PROTOTYPE MODEL OF CARRYING CAPACITY IN TOURISM: THE IMPLEMENTATIONS FOR THE ISLAND OF RHODES - Prokopiou, D.G.; Tselentis, B.S; Mavridoglou, G.; Lagos, D. (European Scientific Journal, ESJ, 2014)
Sustainable tourism can be defined as the tourism that takes full account of its current and future economic, social and environmental impacts, addressing the needs of visitors, the industry, the environment and host communities. From the above definition it is mention that sustainable development ties together concern for the carrying capacity of natural systems with the social and economic challenges faced by humanity. Carrying capacity is defined as the maximum number of people that may visit a tourist destination at the same time, without causing destruction to the physical, economic, sociocultural environment and an unacceptable decrease in the quality of visitors’ satisfaction. Today, controlling tourism growth has become a central policy issue for the tourism trade and it is noteworthy that carrying capacity assessment has become an important tool for facilitating planning and developing policy issues for the industry. In this paper we use present a model for assessment the carrying capacity.It is the first time that we apply the valuation of carrying capacity indicators of Greek islands in a new prototype model, which examines twenty indicators regarding environmental and tourism for the island of Rhodes. Based on the proposed model first the results from Island of Rhodes are compared with the indicatorsfrom all the Greek islands, the islands in North Aegean Archipelagos and the islands in Dodecanese Archipelagos. At least a comparison between the municipalities of Islands of Rhodes is presented.